A latent class analysis of brief postpartum psychiatric hospital admissions. (April 2018) - Shlomi Polachek, Inbal; Fung, Kinwah; Putnam, Karen; Meltzer-Brody, Samantha; Vigod, Simone N.
Abstract: Almost 40% of postpartum psychiatric hospital admissions are brief, lasting 72 h or less. We aimed to identify unique subgroups of women within this group to inform better intervention. All women in Ontario, Canada with a brief postpartum psychiatric admission (≤ 72 h) (2007–2012)(N = 631) were studied using latent class analysis. We identified distinct subtypes of women and compared women within each subtype on post-discharge mental health indicators: physician visits, emergency department (ED) visits and readmissions. We identified four clinically distinct classes: (1)women with no diagnosed mental illness (2 years before delivery) (n = 179; 28.4% of the sample); (2)women with pre-existing history of severe mental illness (i.e. psychosis) (n = 161; 25.5%); (3)women with pre-existing history of non-psychotic mental illness (n = 211; 33.4%); and (4)adolescent rural-dwelling women with alcohol and substance use disorders (n = 80; 12.7%). In the 1 year post-discharge, women in classes 1–3 were more likely to have post-discharge physician visit than women in class 4 (p < 0.05) and were less likely to have a psychiatric ED visit (p < 0.05). Women in class 2 were most likely to be readmitted (p < 0.05). We identified clinically distinct subgroups of women with brief postpartum psychiatric admissions who may each benefit from differing targeted preventive strategies and post-discharge treatment planning. Highlights: We found four clinically distinct subtypes of brief postpartum psychiatric admissions. Targeted screening may help a large subgroup with no mental illness history. Preventive care may prevent some admissions for the three subgroups with pre-existing mental illness. A large group with severe mental illness and high readmission risk requires attention. Young, substance-using women with poor post-discharge outcomes warrant consideration.